The Effect of The Bio-Inspired Airfoil NACA 4415 at High Reynolds Number - Saphira Anggraita Siswanto; James Julian; Fitri Wahyuni; Riki Hendra Purba; Fathin Muhammad Madhudhu; Elvi Armadani (JTERA (Jurnal Teknologi Rekayasa), 2025)
The topic of airfoil modification and its impact on aerodynamic performance is a highly debated issue in aerospace engineering circles. This study examines the effect of the NACA 4415 bio-inspired nose airfoil on its aerodynamic performance by adding spinner dolphin and roughtoothed dolphin geometries to the leading edge using the Computational Fluid Dynamics (CFD) method at a Reynolds number of Re = 106. Simulations were conducted to analyze changes in the lift coefficient (Cl), drag coefficient (Cd), and moment coefficient (Cm), which serve as indicators of aerodynamic performance and stability. The results show that the baseline NACA 4415 airfoil produces the highest lift and the lowest drag overall, making it suitable for applications requiring maximum lift and minimum drag. Spinner dolphins has a smaller percentage increase in Cd, at 41.933%, compared to the baseline. In contrast, roughtoothed dolphins with an average percentage of 56.004% compared to the baseline exhibit a higher percentage increase in Cd. Conversely, in the Cl data, the percentage decreased in   dolphins has a larger average, namely -14.607%, compared to the baseline, whereas the spinner dolphin type only has an average of -8.713%. In the Cm data, the Roughtoothed Dolphin and Spinner Dolphin have higher and more stable Cm than NACA 4415. This study confirms that bio-inspired modifications can significantly impact aerodynamic performance, depending on operating conditions.